2019
DOI: 10.1016/j.brs.2019.06.021
|View full text |Cite
|
Sign up to set email alerts
|

After-effects of 10 Hz tACS over the prefrontal cortex on phonological word decisions

Abstract: Introduction: Previous work in the language domain has shown that 10 Hz rTMS of the left or right posterior inferior frontal gyrus (pIFG) in the prefrontal cortex impaired phonological decision-making, arguing for a causal contribution of the bilateral pIFG to phonological processing. However, the neurophysiological correlates of these effects are unclear. The present study addressed the question whether neural activity in the prefrontal cortex could be modulated by 10 Hz tACS and how this would affect phonolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 91 publications
3
32
0
Order By: Relevance
“…On the contrary, alpha-tACS impaired visual and phonological discrimination performance [44,45]. Some frequencies led to no performance changes with online stimulation (i.e., theta-and beta-tACS) [52,54]. Online stimulation aiming to influence phase coherence (see Figure 1C; here: anti-phase, bi-hemispheric gamma-tACS) impaired visual motion change detection.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the contrary, alpha-tACS impaired visual and phonological discrimination performance [44,45]. Some frequencies led to no performance changes with online stimulation (i.e., theta-and beta-tACS) [52,54]. Online stimulation aiming to influence phase coherence (see Figure 1C; here: anti-phase, bi-hemispheric gamma-tACS) impaired visual motion change detection.…”
Section: Discussionmentioning
confidence: 92%
“…Moliadze and colleagues [52] applied alpha-tACS preceding a phonological decision task. The participants listened to words and decided whether they consisted of two or three syllables.…”
Section: Auditory Perceptionmentioning
confidence: 99%
“…We used the optimal electrode arrangement based on computational modeling from individual MRIs to target the current flow with the highest specificity at the mPFC-ACC, with maximum current density in the ACC, to investigate the post-modulatory θ-tACS effect on inhibitory control. Based on the evidence from previous studies that confirmed the alteration of inhibitory control performance during θ-tACS neuromodulation (van Driel et al, 2015;Moliadze et al, 2019), we extended the experiment to include a θ-tACS condition that modulated the ACC indirectly through MFC.…”
Section: Discussionmentioning
confidence: 99%
“…Transcranial Alternating Current Stimulation (tACS) enables modulation of endogenous oscillations at the pacing rate (Paulus, 2011;Ali et al, 2013;Antal and Paulus, 2013;Herrmann et al, 2013;Antal and Herrmann, 2016), inducing frequency-specific activity changes (Vossen et al, 2015;Witkowski et al, 2016) and the subsequent induction of synaptic changes via neuronal plasticity, providing a post-modulation effect on brain oscillation activity (Antal et al, 2008;Zaehle et al, 2010;Vossen et al, 2015;Berger et al, 2018;Moliadze et al, 2019). The effect of various tACS frequencies on cognition was tested (Sela et al, 2012;Hoy et al, 2015;van Driel et al, 2015;Vosskuhl et al, 2015;Wischnewski et al, 2016;Fusco et al, 2018;Pahor and Jaušovec, 2018;Lehr et al, 2019;Moliadze et al, 2019). Specific cognitive abilities were significantly modified mostly by the theta frequency tACS (θ-tACS; Sela et al, 2012;van Driel et al, 2015;Vosskuhl et al, 2015;Wischnewski et al, 2016;Fusco et al, 2018Fusco et al, , 2020Pahor and Jaušovec, 2018;Lang et al, 2019;Lehr et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 17 - 19 In particular, the immediate effects and sustained after effects of tACS on alpha activity have been well established. 20 - 24 In auditory research, tACS has been useful in making causal connections between brain activity and the hearing process; where brain recording methods can only infer correlation between neural entrainment and cognitive processes, 25 tACS makes it possible to infer causal links between the 2 by enhancing or disrupting entrainment to a certain frequency. 26 , 27 Using these methods, evidence has been found that neural entrainment plays an active role in speech perception, instead of merely being a result of it.…”
Section: Introductionmentioning
confidence: 99%